Pengaruh Motivasi Kerja dan Pengembangan Kompetensi terhadap Kinerja Guru pada SMP Negeri 5 Abiansemal di Badung (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
This investigate points to decide the impact of work inspiration and competency improvement on educator execution at SMP Negeri 5 Abiansemal in Badung. The investigate strategy utilized is quantitative. The investigate area is at SMP Negeri 5 Abiansemal in Badung. The test utilized was 34 respondents. The information investigation procedures utilized are Legitimacy Test, Unwavering quality, Classical Presumptions, Different Direct Relapse, Coefficient of Assurance, T Test and F Test. Based on the investigate comes about, the comes about appear that work inspiration features a critical positive impact on educator execution as prove by the t esteem = 3.239 and the noteworthiness esteem = 0.000, competency improvement encompasses a critical positive impact on educator execution as prove by the tcount = 2.999 and centrality esteem = 0.000, and at the same time work inspiration and competency advancement have a positive and critical impact on educator execution as prove by the Fcount = 25.660 and importance esteem = 0.000. The greatness of the impact of the free variable on educator execution is 59.9%. The recommendation in this inquire about is that the leaders of SMP Negeri 5 Abiansemal in Badung ought to make a arrangement of giving grants to the leading instructors, continuously give support to instructors and intermittently give preparing to instructors, so that afterward instructors will be able to make strides their instruction.